ANALISIS PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP KINERJA KARYAWAN (Studi pada PT. Apac Inti Corpora Bawen Jawa Tengah Unit Spinning 2) - Ilfani, Grisma; Nugraheni, Rini (Diponegoro Journal of Management, 2013)
The performance is a result of the quality and quantity of work achieved by an officer in carrying out his duties in accordance with the responsibilities assigned. One of the causes of the declining performance of the employee is occupational safety and occupational health. This study aims to analyzed the effect of occupational safety and occupational health on employees performance at PT. Apac Inti Corpora Bawen Jawa Tengah Unit Spinning 2.Sampling in this research was using the method of random sampling by taking a sample as much as 81 respondents on PT. Apac Inti Corpora Unit Spinning 2 and using analyze regression method. Collecting primary data is done using the methods a questionnaire, while collecting secondary data done with a method of literature and the source of the internet.Based on the results of the calculation of regression analysis it can be concluded that the variable that have the greatest influence on the performance of the employee is Occupational health (X2) with the value of coefficient regression of 0,371, while the Occupational safety variable (X1) has a value of coefficient regression of 0,272.